Literature Review: Study on the Utilization of Solar Power Plants (PLTS) as an Effort to Increase Electricity Access in Rural and Remote Areas - Firdiansyah; Putra, Asri Eka; Rusdianasari (International Journal of Research in Vocational Studies (IJRVOCAS), 2025)
The abundant potential of solar energy in Indonesia needs to be utilized effectively, especially by houses in areas that do not have electricity. This study aims to discuss solar power generation systems for households without access to electricity in rural and remote areas. The method is a literature review to review relevant studies related to solar power plants in rural and remote areas. The results found that the use of PV can increase access to electricity in remote or rural areas, that can increase the Electrification Ratio and Electrified Village Ratio in an area, increase the role of renewable energy (RE), and reduce GHG (Green House Gas) emissions. It is necessary to pay attention to the provision of initial investment costs, research and development, training and capacity building of human resources, and control over product quality.